1996
DOI: 10.1152/ajpcell.1996.270.4.c1088
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for receptor-mediated mineralocorticoid action in rat osteoblastic cells

Abstract: Aldosterone significantly enhanced the proliferation of osteoblastic cells from rat calvaria, and this effect was inhibited by RU 26752 and ZK 91587, two antagonists specific to the mineralocorticoid receptor (MCR). In addition, aldosterone inhibited the activity of alkaline phosphatase, a marker of the osteoblastic phenotype, and this effect was also reversed by RU 26752. Cytoplasmic staining of MCR was observed in rat calvaria osteoblasts incubated with a specific polyclonal antiserum raised against rat kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…Thus, lymphocytes are endowed with the MCR although its functional relevance there remains unknown. 4 A comparable study with murine osteoblastic cells revealed altered growth response with steroids targeted for specificity to the MCR 18 and a similar situation could well be envisioned with hematopoietic cells.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Thus, lymphocytes are endowed with the MCR although its functional relevance there remains unknown. 4 A comparable study with murine osteoblastic cells revealed altered growth response with steroids targeted for specificity to the MCR 18 and a similar situation could well be envisioned with hematopoietic cells.…”
Section: Introductionmentioning
confidence: 79%
“…To assess multiplication, 80 000 cells were transferred to 12-well tissue culture plates (six per sample), exposed to the desired combination of steroids dissolved in ethanol (1% final) in a serum-free medium for 3 days, and finally counted manually with the aid of a hematocytometer. 18 The condensation of chromatin was measured by a fluorometric procedure with the aid of Hoechst 33342 (Germany). For this purpose, 4 × 10 4 cells were grown to 80-90% confluence in 96-well tissue culture plates and reincubated in RPMI 1640 supplemented with glutamine, antibiotics, and 2% FCS.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…The cells were trypsinized and counted with the aid of either a cell counter or a hematocytometer [16,17,19].…”
Section: Cell Multiplicationmentioning
confidence: 99%
“…The anti-MCR serum was raised by immunizing rabbits with the protein purified biochemically from rat kidney in the presence of RU 26752 that binds specifically to this receptor [11,19]; the IgG fraction was obtained by fractionating the serum through a diethylaminoethanol-Trisacryl column [16,17].…”
Section: Chemicals and Reagentsmentioning
confidence: 99%